SOCIAL ENTREPRENEURSHIP IN BUILDING FINANCING MANAGEMENT - Masruroh, Iin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The purpose of this paper is about social entrepreneurship in building and managing costs. Social entrepreneurship is a concept that can solve social problems with an ideal, directed and sustainable social entrepreneurship business approach that can be carried out through educational activities. The research method is descriptive qualitative while the sample is determined by purposive random sampling method. Data collection used a combination of approaches, including surveys, observations, field studies, and interviews and research locations conducted at SMAN 4 Jember. The results of the study show that the implementation of social entrepreneurship development is carried out in the form of snack entrepreneurs, ATK, and food and clothing cooperatives. This program is expected to be able to help generate income for educators in these institutions and have business independence as well as social sensitivity and provide a balance of academic ability, attitude and work in the framework of community self-development, both as professional, independent and innovative social entrepreneurs. The results of social entrepreneurship in managing costs have components that are obtained, namely social value, leaders innovate, economic activity, and leaders carry out cost control. This is expected to create a social business that can have a positive impact on educational institutions and improve people's welfare